The Effects of Herding Behavior, Anchoring Bias, and Availability Bias on Retail Investors' Trading Behavior - Nevanda Julya Rizki; Ni Putu Ayu Sinta Widiasih; Amelia Wardatus Rizki; Dian Pramesti Agustina; Maria Yovita R. Pandin (HUMAN: Journal of Social Humanities and Science, 2026)
This study aims to analyze the influence of herding behavior, anchoring bias, and availability bias on retail investor trading behavior, especially among students as novice investors. The phenomenon of increasing the number of retail investors in Indonesia has not been fully balanced with good analytical skills, so investment decisions are often influenced by psychological factors. This study uses a descriptive qualitative approach through an open questionnaire that is distributed to students who have experience or interest in investment activities. The results showed that although the majority of respondents began to show a tendency to think more rationally and independently, the three behavioral biases still had an influence on decision-making. Herding behavior arises when respondents feel more confident following the majority, anchoring bias appears through the habit of making the initial price the main reference, while availability bias can be seen from the dependence of some respondents on information that often appears such as news and social media. This study confirms that retail investors are still in the transition stage towards more mature and rational investment behavior. Improving financial literacy and understanding of investment psychology is needed so that trading decisions can be made more objectively and measurably, thereby minimizing the risk of losses in the capital market.